EFEKTIVITAS EXPERIENTIAL LEARNING DALAM MENINGKATKAN PEMAHAMAN MATERI PSIKOLOGI PERKEMBANGAN - Ince Prabu Setiawan Bakar; Triani Arfah (AIJER: Algazali International Journal Of Educational Research, 2019)
Abstract: Effectiveness of Experiential Learning in Improving Understanding of Developmental Psychology Materials. The purpose of this research is to find out the improvement of students' active learning in developmental psychology subjects with experiential learning theory methods and to find out the increase in student learning outcomes in developmental psychology subjects with experiential learning theory methods. This research uses an experimental method. The learning method carried out in this experiment uses the experiential learning model. The hypothesis in this study is the understanding of the psychology of PG-PAUD students' developmental material taught by experiential learning method is higher than the group that does not use experiential learning method. The sample in this study were PG-PAUD students who were taking developmental psychology courses. To test the results used t-test results. The results showed the use of experiential learning learning models affect student learning outcomes in PG-PAUD based on Sig. (2-tailed) <0.05, it is known that there is a significant difference between the learning outcomes of the experimental class and the control class.